Replacing Concentrate with Yeast- or EM-Fermented Cassava Peel (YFCP or EMFCP): Effects on the Feed Intake, Feed Digestibility, Rumen Fermentation, and Growth Performance of Goats - Pongsatorn Gunun; Anusorn Cherdthong; Pichad Khejornsart; Metha Wanapat; Sineenart Polyorach; Walailuck Kaewwongsa; Nirawan Gunun (My University, 2023)
The goal of this study was to improve the nutritional value of cassava peel by using yeast (Saccharomyces cerevisiae) or effective microorganisms (EM), then use it as a replacement for concentrate, and examine the effects on the feed intake, feed digestibility, rumen fermentation, and growth performance of goats. The experimental design was a randomized complete block design (RCBD), and the dietary treatments were (1) concentrate, (2) replacement of the concentrate by yeast-fermented cassava peel (YFCP) at 50% and (3) replacement of the concentrate by EM-fermented cassava peel (EMFCP) at 50%. Twelve goats were given concentrate based on their treatments at a rate of 1.5% of their body weight. Rice straw was used as roughage and fed freely. It was found that the crude protein (CP) content of the cassava peel from 2.1% to 13.7-13.8% after 14 days of fermentation. Moreover, there were no significant differences between the treatments in terms of the feed intake, feed digestibility, ruminal pH, blood urea nitrogen concentration, volatile fatty acid profile, overall average daily gain, and feed efficiency. However, the cost of the feed per gain decreased when the YFCP or EMFCP was used instead of the concentrate. Based on the results of this experiment, it was possible to conclude that yeast or EM might be utilized as microorganisms to increase the nutritional value of cassava peel. Moreover, YFCP or EMFCP can replace concentrate by up to 50% without an impact on the feed intake, feed digestibility, rumen fermentation characteristics, and the growth performance; whereas, it can reduce the feed cost per gain up to 32%.
Keywords: Cassava research and cyanide